Kebangkitan Party ID: Analisis Perilaku Memilih dalam Politik Lokal di Indonesia - Haryanto, - (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This article explains that the party identification (party ID) has become the main factor of voting behavior in local politics in Indonesia. Voters no longer dominant consider the proximity factor, both ethnic and regional proximity in determining vote choice, as a general conclusion that has been used to explain voting behavioral in local politics in Indonesia. This article confirms that voters tend to conform to the party then make a choice their voices to candidates that are offered by the party.